The triffin dilemma again - Edoardo Campanella (Kiel Institute for the World Economy (IfW), 2009)
Tiny changes in the American monetary policy can have dramatic effects on the rest of the world because of its double role of national and international currency. This is what I call the Triffin dilemma, an ever green concept in international finance. In the paper I show how it works through three examples: price of commodities, dollarization, and the international financial position of the US. I argue that to solve this situation, it would be important to create a more democratic monetary system, in which all the countries have a decision weight. In particular, I think that globalization and regionalization should be the two forces leading towards the new monetary system. The main economies should adopt the same currency through a system of fixed exchange rates (global money); developing countries should create regional monetary unions (regional money), preserving the real exchange rate as real shock absorber, but gaining in terms of time consistency and credibility.
Keywords: F33; 330; Triffin dilemma; global currency; regional monetary union; dollarization; Internationales Währungssystem; Reform; Globalisierung; Handelsregionalismus; Agent-based Model; Welt; Geldpolitik; Währungssubstitution; Reservewährung; US-Dollar; USA